Regional green transition: Cases of Polish and Russian regions - Męczyński, Michał; Ciesiółka, Przemysław (Quaestiones Geographicae, 2022)
The green transition unfolding on a global scale is much less studied at the regional level, although its outcomes and management are strongly place-specific. This article presents a comparative study of green transition strategies in the Silesian Voivodeship (Poland) and the Khanty-Mansiysk Autonomous Okrug (KMAO) – Ugra (Russia), based on a qualitative content analysis of regional legislation and strategies. The regions share common specialisation in fossil fuel mining and have inherited some features of post-socialist economies. Research shows three common features of green transition policies in the studied regions. Firstly, much attention is paid to the dissemination of information about green transition and its benefits. Secondly, research on various green subjects and educational programmes for green market requirements are developed. Thirdly, it is planned for renewables to have a larger proportion in regional energy mixes. By mid-century, both regions are expected to reach climate neutrality, although by using different paths of development. Coal mines are planned to be closed down in the Silesian Voivodeship by 2050, while the KMAO – Ugra will retain its oil-mining specialisation but diversify it with hydrogen production.